The tomb of shadows - Lerangis, Peter (London : HarperCollins Children's Books, 2014)
Teens Jack, Marco, Aly, and Cass begin a quest to find seven pieces of Atlantis' power that were hidden long ago and that will, if returned to Atlantis, save them from certain death due to the genetic abnormality that also gives them superior abilities.
4.2
5-8.
5-8
Keywords: Ability -- Juvenile fiction; Atlantis (Legendary place) -- Juvenile fiction; Friendship -- Juvenile fiction; Ability -- Fiction; Adventure and adventurers -- Fiction; Atlantis (Legendary place) -- Fiction; Friendship -- Fiction; Science fiction; Ability -- Fiction; Adventure fiction; Atlantis (Legendary place) -- Fiction; Friendship -- Fiction; Science fiction; Adventure fiction; Science fiction